TECHNOLOGY OF TRAINING VOLUNTEERS TO WORK WITH ATHLETES WITH DISABILITIES - Stepaniuk, O. V.; Kohut, I. O. (Rehabilitation and Recreation, 2025)
Purpose. This study aims to develop and substantiate a technology for training volunteers to work with athletes with disabilities, addressing the growing demand for qualified support in adaptive sports and reflecting current international trends in volunteer management and inclusive education.Material and methods. A mixed-methods approach was applied, combining theoretical analysis, synthesis, and generalisation with a sociological survey and mathematical statistics. The empirical base included 82 respondents — 34 participants of the course “Explore the World of Volunteering in the Special Olympics Movement” and 48 third-year students of the National University of Physical Education and Sport of Ukraine. Quantitative and qualitative data were analysed to identify socio-humanistic effects and determine key organisational and methodological conditions for volunteer training.Results. The study developed a comprehensive three-stage technology (preparatory, implementation, and evaluation phases) for training volunteers in adaptive sports. The model integrates contemporary motivational, organisational, and pedagogical components of volunteering and aligns them with the principles of inclusion and social responsibility. Correlation analysis revealed strong interrelations among the identified conditions — cooperation with sport organisations, presence of qualified specialists, evaluation mechanisms, and structured methodological support – confirming their systemic influence on the efficiency of training outcomes. The implementation of the proposed technology in educational practice demonstrated its effectiveness in enhancing professional competence, empathy, communication skills, and sustained motivation for volunteer engagement. The socio-humanistic impact was manifested in increased awareness of inclusion values and a stronger commitment to supporting people with disabilities through sport. The results can inform curriculum design, staff development initiatives, and policy frameworks promoting inclusive volunteering across educational and sports institutions.Conclusions. The developed technology constitutes an effective framework for advancing volunteer programmes in adaptive sports. It contributes to the improvement of training quality, institutional collaboration, and the dissemination of innovative forms of volunteer activity. The model provides practical guidance for universities, sports federations, and non-governmental organisations seeking to strengthen inclusive sport systems and foster humanistic values within local communities.